Cross-sectional study of paediatric case mix presenting to an emergency centre in Cape Town, South Africa, during COVID-19 - Lembi Magano Akuaake; Clint Hendrikse; Graeme Spittal; Katya Evans; Daniël Jacobus van Hoving (BMJ Publishing Group, 2020)
Objective To describe and compare the effect of level 5 lockdown measures on the workload and case mix of paediatric patients presenting to a district-level emergency centre in Cape Town, South Africa.Methods Paediatric patients (<13 years) presenting to Mitchells Plain Hospital were included. The level 5 lockdown period (27 March 2020-30 April 2020) was compared with similar 5-week periods immediately before (21 February 2020-26 March 2020) and after the lockdown (1 May 2020-4 June 2020), and to similar time periods during 2018 and 2019. Patient demographics, characteristics, International Statistical Classification of Diseases and Related Health Problems, 10th Revision (ICD-10) diagnosis, disposition and process times were collected from an electronic patient tracking and registration database. The χ2 test and the independent samples median test were used for comparisons.Results Emergency centre visits during the lockdown period (n=592) decreased by 58% compared with 2019 (n=1413) and by 56% compared with the 2020 prelockdown period (n=1342). The proportion of under 1 year olds increased by 10.4% (p<0.001), with a 7.4% increase in self-referrals (p<0.001) and a 6.9% reduction in referrals from clinics (p<0.001). Proportionally more children were referred to inpatient disciplines (5.6%, p=0.001) and to a higher level of care (3.9%, p=0.004). Significant reductions occurred in respiratory diseases (66.9%, p<0.001), injuries (36.1%, p<0.001) and infectious diseases (34.1%, p<0.001). All process times were significantly different between the various study periods.Conclusion Significantly less children presented to the emergency centre since the implementation of the COVID-19 lockdown, with marked reductions in respiratory and infectious-related diseases and in injuries.